Ball-milling enables highly selective solvent-free N-tert-butoxycarbonylation for activation of amides. Issue 29 (16th July 2020) - Shi, Weijia; Sun, Guoping; Zou, Gang
Graphical abstract: Highlights: Mechanochemical solvent-free N - tert -butoxycarbonylation of amides. High chemoselectivity with respect to NH acidity. Capable of one-pot two-step sequential transformations. Abstract: A ball-milling enabled chemoselective activation of amides via N - tert -butoxycarbonylation catalyzed by 4-dimethylaminopyridine is described under solvent-free conditions. High chemoselectivity with respect to NH acidity of amides has been observed. A one-pot two-step procedure for selective esterification of amides has been demonstrated in model reaction of benzamides with p- cresol and benzyl alcohol.